Pengaruh Pengaruh Sumber Belajar Terhadap Motivasi Belajar Pada Mata Pelajaran Ekonomi Kelas X di SMA Islam Darussalam Depok - adinda webby handayani (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Bima, 2020)
The aim of this research is to find out how much influence learning resources have on learning motivation. The school that was the object of this study was Islam Darussalam High School. The research method used in this study is a survey method with a correlational approach that is to determine the effect of learning resources on learning motivation. The population in this study were grade X students in Depok's Islamic High School, totaling 103 samples, found 82 people were done using simple random sampling technique. Data collection methods used in this study were through a questionnaire (questionnaire) with a total of 30 items. Through calculations obtained a rxy of 0.545 which means there is sufficient influence between learning resources on learning motivation. Based on the analysis of the coefficient of determination of the contribution of variable x (learning resources) of 29.70% and the remaining 52.6656% is determined by the contribution of other factors not examined in this study. These effects have been tested using statistical hypothesis testing which obtained the results of tcount 5.816> t table 1.664. This shows that there is a positive and significant effect between the variable x (learning resources) and the y variable (learning motivation).